Comparison of Risk Factors for Priority Non-Communicable Diseases in Bandung Regency Hajj Pilgrims in 2024 - Yeni Suryamah; Oka Septiriani; Neneng Kusmawati; Khalina Puspitasari (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
The most common diseases suffered by Indonesian hajj pilgrims are non-communicable diseases (NCDs). To optimize the health istita'ah policy of the Ministry of Religion, further analysis is needed regarding the risk factors for NCDs in hajj pilgrims. This study aims to compare the risk factors for priority NCDs (hypertension and diabetes mellitus) in hajj pilgrims in Bandung Regency. The research design used was a case-control study with secondary data from the Integrated Hajj Computerized System for Health (Siskohatkes). The number of samples was 178 hajj pilgrims for each case and control group. Data analysis was carried out using the logistic regression analysis method. The results showed that age (OR=4.34; 95%CI=1.45-13.02) and comorbidities (OR=7.65; 95%CI=4.59-12.73) were risk factors for hypertension in hajj pilgrims. Age (OR=2.65; 95%CI=1.14-6.15) and comorbidities (OR=7; 95%CI=4.31-11.34) are also risk factors for diabetes mellitus in hajj pilgrims. Hajj pilgrims with a high-risk age category (≥40 years) or comorbidities are at greater risk of experiencing hypertension than diabetes mellitus. Thus, health coaching for hajj pilgrims must include lifestyle modification and education on routine control compliance.